Blood in the water : a Gregor Demarkian novel - Haddam, Jane, 1951-2019- (Haddam, Jane, 1951-2019- Gregor Demarkian books., 2012)
In the wake of a double murder involving a woman who has gone missing amid rumors of an affair with a teenager, Gregor Demarkian's investigation targeting her jealous rich husband is thrown into chaos by the discovery of a stranger's body at the scene.